Relation between Long-term Activity and Luminosity of the Pre- and Post-novae CT Ser and V446 Her - Vojtěch Šimon (The Astronomical Journal, 2023)
We show a relation of the pre- and post-nova activity of CT Ser (nova 1948) and V446 Her (nova 1960), known to have remarkably similar orbital periods P _orb . We use both photographic and CCD photometric observations. Post-nova CT Ser shows a nova-like high-state activity with only a slight decrease of absolute magnitude M _opt . In the interpretation, its M _opt is above the region of the thermal-viscous instability (TVI) regime, so the disk is ionized out to its outer rim, similarly to before its classical nova (CN) outburst. On the contrary, V446 Her started its CN outburst from the TVI regime. Extensive changes in activity type in years after CN outburst were observed in V446 Her. The features consistent with the dwarf-nova outbursts appeared at most three decades after the end of the CN outburst. It suggests that its disk transitioned into the TVI region in that it was before its CN outburst. The pre-nova and post-nova states of activity did not change significantly for a given system, except for several decades after the CN outburst. Even pre-novae and post-novae with mutually similar P _orb , hence secondary star (donor) spectral types and dimensions and disk radii, can show largely discrepant M _opt and disk states in the similar epochs (several decades) surrounding the CN outburst.